Optimization of Quality Control for Non-Dairy Creamer Products at PT. XYZ Based on Statistical Process Control (SPC) to Improve Production Efficiency - Sulkhan, Sulkhan; Alex, Alex (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The competitive dynamics of the Fast-Moving Consumer Goods (FMCG) industry, particularly in the non-dairy creamer sector, necessitate stringent quality control to ensure production efficiency. This study aims to analyze process stability, evaluate process capability, and identify root causes of quality variability in the production of non-dairy creamer using the Statistical Process Control (SPC) approach. Critical to Quality (CTQ) parameters, including net weight and moisture content, were monitored over 30 production days with a total of 150 and 210 observations, respectively. The methodology employed Anderson-Darling normality tests, X̅ ─ R control charts, and process capability indices (Cp and Cpk). The results indicated that the moisture content process was stable and highly capable (Cpk = 1.85). However, the net weight analysis revealed a special cause variation in subgroup 15, exceeding the Upper Control Limit (UCL), despite maintaining an overall excellent capability (Cpk = 1.70). Root cause analysis using a Fishbone Diagram identified dust accumulation on the load cell sensors and inadequate cleaning SOPs as the primary factors for the over-filling anomaly. This research formulates corrective recommendations, including the implementation of an automated self-cleaning system and digital monitoring, to minimize rework costs and optimize raw material usage, thereby enhancing overall production efficiency.